Efektivitas Pelayanan Publik Berbasis Digital di Dinas Kearsipan dan Perpustakaan Provinsi Gorontalo - Umi Rohmatur Rosidah; Zuchri Abdussamad; Irawaty Igirisa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the effectiveness of digital-based public services at the Gorontalo Provincial Archives and Library Office using the three dimensions of organizational effectiveness proposed by Duncan (Steers, 2015): goal attainment, integration, and adaptation. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving seven informants. The findings indicate that, from the goal attainment dimension, several digital services, including digital membership registration, the Online Public Access Catalog (OPAC), and e-book services, have been made available. However, the number of iArpus users has continuously declined over the past three years, and book lending services are still conducted manually. From the integration dimension, 22 Standard Operating Procedures (SOPs) and memoranda of understanding with various partners have been established. Nevertheless, the lack of regular coordination has led to digital service processes that are not yet fully integrated. Along the adaptation dimension, a gap exists between younger employees, who tend to be more adaptable to technological change, and senior employees, whose digital literacy remains limited. This challenge is further compounded by constraints in infrastructure and budget allocation. The study concludes that the effectiveness of digital-based public services at the institution has not yet reached an optimal level. Therefore, continuous and integrated improvements, across the dimensions of goal attainment, integration, and adaptation arom renecessary to enhance the effectiveness of digital public service delivery.